A thermal and electrochemical properties research on gel polymer electrolyte membrane of lithium ion battery. (December 2016) - Li, Libo; Ma, Yue; Wang, Wentao; Xu, Yanping; You, Jun; Zhang, Yonghong
Abstract: N-methyl-N-propyl-piperidin-bis(trifluoromethylsulfonyl)imide/bis(trifluoromethylsulfonyl) imide lithium base/polymethyl methacrylate(PP13 TFSI/LiTFSI/PMMA) gel polymer electrolyte (GPE) membrane was prepared by in situ polymerization. The physical and chemical properties were comprehensively discussed. The decomposition characteristics were emphasized by thermogravimetric (TG-DTG) method in the nitrogen atmosphere at the different heating rates of 5, 10, 15 and 20 °C min −1, respectively. The activation energy was calculated with the iso-conversional methods of Ozawa and Kissinger, Friedman, respectively, and the Coats-Redfern methods were adopted to employ the detailed mechanism of the electrolyte membrane. The equation f ( α )=3/2[(1− α ) 1/3 −1] was quite an appropriate kinetic mechanisms to describe the thermal decomposition process with an activation energy ( E α ) of 184 kJ/mol and a pre-exponential factor ( A ) of 1.894×10 11 were obtained. Highlights: Conductivity E a of PP13 TFSI/LiTFSI/PMMA 35.35 kJ/mol. σ of GPE at the room temperature is 1.07×10 −4  S cm −1 . SEI film electrode and electrolyte is formed after three cycles of CV. E α of 184 kJ/mol and A of 1.894×10 11 are obtained. f ( α )=3/2[(1− α ) 1/3 −1] describes thermal decomposition process.